DEVELOPING DIDACTIC SUPPORT FOR DEVELOPING STUDENTS CREATIVE THINKING SKILLS - Zulxumor Mirzayeva (Bright Mind Publishing, 2025)
The development of students' creative thinking skills is a crucial aspect of modern education, particularly in the field of biology. In Uzbekistan, as in many other countries, fostering creativity among students is an essential part of preparing future professionals who can solve complex scientific and practical problems. This study aims to explore the didactic foundations necessary for the development of creative thinking among students in biological universities. The research examines various approaches to creative thinking, including problem-solving methods, inquiry-based learning, and interdisciplinary strategies that enhance cognitive flexibility. It also highlights the role of digital tools and active learning techniques in promoting innovative thinking among students. By analyzing different didactic models and their effectiveness, the study provides a comprehensive framework for integrating creativity into biological education. The findings emphasize the importance of student-centered methodologies that encourage independent thought, experimentation, and the application of knowledge in novel contexts. The study concludes with recommendations for implementing creative didactic approaches in higher education institutions in Uzbekistan.
Keywords: Creative thinking, didactic approach, problem-solving, inquiry-based learning, biological education, student-centered learning, interdisciplinary strategies.